2003
DOI: 10.1034/j.1600-0706.2003.12226.x
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of rice rats (a Hantavirus reservoir) in southern Chile: feedback structure and non‐linear effects of climatic oscillations

Abstract: Murú a, R., González, L. A. and Lima, M. 2003. Population dynamics of rice rats (a Hantavirus reservoir) in southern Chile: feedback structure and non-linear effects of climatic oscillations. -Oikos 102: 137-145.We studied a fluctuating population of the long-tail rice rat (Oligoryzomys longicaudatus), the main Hantavirus vector in southern Chile, and spanning 19 years of monitoring. We determined that a first-order feedback structure and non-linear effects of Antarctic Oscillation Index (AAOI) and Southern Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 47 publications
1
47
0
1
Order By: Relevance
“…Lara et al (2008) have recently shown that stream flow in the Rio Puelo in Northern Patagonia is significantly correlated with the AAO over 1948-2000 confirming the precipitation linkage. Murúa et al (2003) also found that the AAO correlates with fluctuations in the population density of a native mouse in south-central Chile, suggesting that the available food supply for these grain-eating rodents is controlled by precipitation. The influence of AAO on precipitation may possibly be explained by variations in the blocking activity over the Amundsen-Bellingshausen area west of the Antarctic Peninsula.…”
Section: General Circulation Indices and Rainfall In Southern South Amentioning
confidence: 93%
“…Lara et al (2008) have recently shown that stream flow in the Rio Puelo in Northern Patagonia is significantly correlated with the AAO over 1948-2000 confirming the precipitation linkage. Murúa et al (2003) also found that the AAO correlates with fluctuations in the population density of a native mouse in south-central Chile, suggesting that the available food supply for these grain-eating rodents is controlled by precipitation. The influence of AAO on precipitation may possibly be explained by variations in the blocking activity over the Amundsen-Bellingshausen area west of the Antarctic Peninsula.…”
Section: General Circulation Indices and Rainfall In Southern South Amentioning
confidence: 93%
“…climate) influence population processes (Royama 1992, Stenseth et al 2002. On the other hand, the existence of non-linearity in climatic forcing has been recently explored in terrestrial (Murúa et al 2003) and marine ecosystems (L. Ciannelli et al unpubl. ).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo, los autores postulan que el aumento en el número de casos (de SCPH) en esos años en la X Región sería (hipotéticamente) el resultado de una cascada trófica catalizada inicialmente por el Fenómeno del Niño (ENSO, por sus siglas en inglés) ocurrido 1 ó 2 años antes. Sin embargo, la dinámica poblacional de roedores (en particular de O. longicaudatus) en el Sur de Chile es entendida por procesos más complejos que no sólo consideran la incidencia de las precipitaciones derivadas de un fenómeno ENSO 6 . Y esto no necesariamente resulta en un aumento del número de casos de SCPH.…”
Section: Sr Editorunclassified